Src kinase: Key effector in mechanosignalling - Koudelková, Lenka; Brábek, Jan; Rosel, Daniel (International journal of biochemistry and cell biology, 2021)
Cells have developed a unique set of molecular mechanisms that allows them to probe mechanical properties of the surrounding environment. These systems are based on deformable primary mechanosensors coupled to tension transmitting proteins and enzymes generating biochemical signals. This modular setup enables to transform a mechanical load into more versatile biochemical information. Src kinase appears to be one of the central components of the mechanotransduction network mediating force-induced signalling across multiple cellular contexts. In tight cooperation with primary sensors and the cytoskeleton, Src functions as an effector molecule necessary for transformation of mechanical stimuli into biochemical outputs executing cellular response and adaptation to mechanical cues.
Keywords: extracelulární matrix; lidé; buněčný převod mechanických signálů; substrátový protein asociovaný s Crk; Gene Expression Regulation; Integrins; cytoskelet; adaptorové proteiny signální transdukční; Transcription Factors; skupina kinas odvozených od src-genu; Humans; protein-serin-threoninkinasy; Mechanotransduction, Cellular; mechanický stres; transkripční faktory; Crk-Associated Substrate Protein; nádory; zvířata; integriny; Cytoskeleton; Animals; Extracellular Matrix; src-Family Kinases; regulace genové exprese; Receptor-Like Protein Tyrosine Phosphatases, Class 4; Stress, Mechanical; Adaptor Proteins, Signal Transducing; Protein Serine-Threonine Kinases; Neoplasms; tyrosinfosfatasy receptorového typu, třída 4